Can we properly model the neutron monitor count rate?. Issue 9 (26th September 2015) - Gil, Agnieszka; Usoskin, Ilya G.; Kovaltsov, Gennady A.; Mishev, Alexander L.; Corti, Claudio; Bindi, Veronica
Abstract Neutron monitors provide continuous measurements of secondary nucleonic particles produced in the atmosphere by the primary cosmic rays and form the main tool to study the heliospheric modulation of cosmic rays. In order to study cosmic rays using the world network of neutron monitor and needs to be able to model the neutron monitor count rate. Earlier it was difficult because of the poorly known yield function, which has been essentially revisited recently. We have presented a verification of the new yield function of the standard neutron monitor (NM) using a recently released data on the direct in situ measurements of the galactic cosmic rays energy spectrum during 2006–2009 (the period of the record high cosmic ray flux) by Payload for Antimatter Matter Exploration and Light‐nuclei Astrophysics spaceborne spectrometer, and on NM latitude surveys performed during the period of 1994–2007, including periods of high solar activity. We found a very good agreement between the measured count rates of sea level NMs and the modeled ones in very different conditions: from low to high solar activity and from polar to tropical regions. This implies that the count rate of a sea level neutron monitor can be properly modeled in all conditions, using the new yield function.